Robotics Development Using Real-Time Embedded System - Pinto, Matheus; Oliveira, André (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Robotics is an application class that requires the use of real-time systems (RTS) when applied to projects that needs timing constraints. In this article will be presented the basic concepts about RTS and how to apply them in the creation of robots with hard real-time requirements, using as case study a low cost robot. To the best of our knowledge, a paper presenting how create a robotic system with the use of RTS easy to replicate has not been provided so far.